HISTORICAL STAGES OF FORMATION AND DEVELOPMENT OF INTERNAL CONTROL - KOZACHENKO, ANNА (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights the views of scientists on the allocation of periods (stages) in the history of internal control, which differ in the following features: the emergence and development of socio - economic relations that existed at different times; diversification of objects and subjects of control; complicating the tasks of control over the different levels of development of productive forces and equipment of each society; specific methodological techniques. Thus, the first manifestations of control are observed during the period of primitive communal system. The period of slavery is considered the stage of the emergence of internal control. Characteristic of this period was physical coercion to work. In the period of the feudal system, the peculiarities of the development of socio-economic formation of European states are the distinction between external and internal audit, and accounting registers to reflect the facts of economic life, which served for entries in the accounts of the General Ledger. In addition, control activities were manifested in the movement of credit and settlement transactions between buyers, in settlements between buyers and banks, in production processes and private ownership of the means of production. The capitalist system of production did not require many special control bodies, and its functions were carried out directly by the owners of the means of production. The basis of capitalism was the private property of the bourgeoisie on the means of production, but not on the worker, who at that time received more freedom. It was during the communist formation that thorough work was carried out on the methodological support of internal economic control, but its active development began after the declaration of independence of Ukraine, by borrowing the foundations in foreign countries. Thus, the periodization presented in the article helps to trace the historical aspect of the development and formation of internal control as a control system as a whole, in a certain period of time in which.
Keywords: control; internal economic control; primitive communal system; slave; feudal; communist; capitalist stages